The Effects of Heavy Metal Contamination on Liver Function in a Rat Model - Yuliana, Ida; Triawanti, Triawanti; Prenggono, Muhammad Darwin; Oktaviyanti, Ika Kustiyah; Asnawati, Asnawati; Ulfah, Fahrina; Maulana, Irfan (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background:  Mining activities in South Kalimantan have been widely associated with the emergence of various health issues through heavy metal contamination in the water. Previous studies have demonstrated that the presence of heavy metals has an impact on physiological alterations inside many organs, notably the liver.Objective: The study aimed to determined the impact of liver damaged from heavy metal of lead (Pb), cadmium (Cd), and mercury (Hg), and the combination of the three in rat model.Methods: Our research used the true experiment laboratory method with a post-test group design. Male white rats (Rattus norvegicus), aged 2–6 months and weighing 250–300 grams, were assigned to the control group and the treatment group. Treatment groups were administered orally with water contaminated with heavy metals of Pb, Cd, and Hg orally for 28 days. The serum markers of liver damaged were then measured.Results: The levels of transaminase enzymes (AST and ALT) in the heavy metal-exposed group were increased compared to the control group. However, the increase was not statistically significant (p = 0.247; p = 0.349, respectively). The group exposed to Hg exhibited the highest levels of AST and ALT in comparison to the other groups.Conclusion: Heavy metal exposure tend to raise transaminase enzyme levels, indicating liver damage. Hg exhibited the greatest transaminase value increase of all heavy metals, indicating its highest potential for liver toxicity.